'The Italian Maccabees'. Gender, the sacred and anticlericalism in the cult of the Cairoli family (1859–1871). Issue 1 (1st January 2023) - Tafuro, Azzurra
ABSTRACT: This article focuses on the cult of the Cairolis, a well-known family of Italian patriots from Pavia that became an icon of radical democracy, in order to shed light on patriotic martyrdom during the Risorgimento. Combining political history with cultural and gender history, I will use a wide and varied range of sources (letters, funeral brochures, prayer cards, reliquaries and so on) that will allow me to reconstruct the origins, dissemination, and evolution of the cult of the Cairolis: not only that of the four brothers but also that of the mother, Adelaide Bono – one of the very few female 'martyrs' of the Risorgimento. In this way, it is possible to examine in depth the 'Garibaldian religion' and, especially, the creation of a 'pantheon' of red shirts, namely those volunteers/apostles who, in the radicals' eyes, followed the General/Christ.